Miscommunication challenges in a travel agency: Inwards andoutwards (2022)
Despite the fact that the implementation of the my proposal to the apparent internal communication problem of City Sightseeing could not be carried out due to logistics issues and prioritization of other important activities, this problem undeniably affects the service and the attention towards the public, which consequently affects the reputation of the company. This is evidenced by the low demand that some of our tours have. Even when commercial efforts and operational logistics manage to reach agreements, it seems that it is impossible to search for an effective internal organization, which is clearly achieved through communication and feedback between colleagues and supervisors. Nowadays, success is achieved through helping each other out, since we live in a society where interaction represents an essential part of managing companies, especially when we are required to use virtual platforms to promote products. If employees are unaware of the existence of a communication route that gives them the opportunity to solve problems in a more organized and efficient way, then how can we provide a favorable service that is not so flawed in the customers’ eye?